2000
DOI: 10.1007/s005000000044
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fuzzy Logic is the logic of continuous t-norms and their residua

Abstract: In this paper we prove that Basic Logic (BL) is complete w.r.t. the continuous t-norms on [0,1], solving the open problem posed by Ha Âjek in [4]. In fact, Ha Âjek proved that such completeness theorem can be obtained provided two new axioms, B1 and B2, were added to the original axioms of BL. The main result of the paper is to show that B1 and B2 axioms are indeed redundant. We also obtain an improvement of the decomposition theorem for saturated BL-chains as ordinal sums whose components are either MV, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(160 citation statements)
references
References 2 publications
3
150
2
5
Order By: Relevance
“…BL was indeed shown to be the logic of continuous tnorms and their residua [9,6]. Important many-valued logics, previously studied in mathematical logic in independent settings, such as the Lukasiewicz infinitelyvalued logic or the Gödel-Dummett logic, were then proven to be extensions of BL.…”
Section: Preliminariesmentioning
confidence: 97%
“…BL was indeed shown to be the logic of continuous tnorms and their residua [9,6]. Important many-valued logics, previously studied in mathematical logic in independent settings, such as the Lukasiewicz infinitelyvalued logic or the Gödel-Dummett logic, were then proven to be extensions of BL.…”
Section: Preliminariesmentioning
confidence: 97%
“…A finite t-norm satisfying the divisibility condition is called a divisible finite t-norm. In [23,Corollary 3.7] it is shown that finite BL-chains are also ordinal sums of finite Łukasiewicz and minimum, and their finite ordinal sums.…”
Section: Predicate Fuzzy Logicsmentioning
confidence: 99%
“…By adding to the axiomatization of MTL the axiom ϕ ∧ ψ → ϕ&(ϕ → ψ) we obtain the logic BL, studied in [35] and proved in [23] to be the logic of all the ordered algebraic structures defined by continuous t-norms and their residua over the unit real interval [0, 1].…”
Section: Predicate Fuzzy Logicsmentioning
confidence: 99%
“…Moreover McNaughton theorem [McNaughton, 1951] provides a functional description of its logical functions. Many results about Lukasiewicz logic and MV-algebras can be found in the book [Cignoli et al, 1999]. On the other hand, a completeness theorem for Gödel logic was already given in the fifties by Dummett [1959].…”
Section: Many Valued Logical Systems Based On Fuzzy Set Connectivesmentioning
confidence: 99%
“…These are the well-known infinitely-valued Lukasiewicz [1930] and Gödel [1932] logics 4 which are the logical systems corresponding to the so-called Lukasiewicz and minimum t-norms and their residuated implications respectively (see, for example, [Cignoli et al, 1999;Gottwald, 2001] for excellent descriptions of these logics). Much later, already motivated by research on fuzzy logic, Product logic, the many-valued logic corresponding to Product t-norm and its residuum, was also axiomatized in [Hájek et al, 1996].…”
Section: Bl and Related Logicsmentioning
confidence: 99%